An investigation into laser sintering of nano-hydroxyapatite coated powders for bone tissue applications - Hui, Dominic (2019)
Exploratory routes were undertaken to deposit Nanoparticles (NPs) such as nanohydroxyapatite (nHA) onto control substrate particles namely Polyamide 12 (PA12) and biodegradable particles such as Poly Lactic Acid (PLA). This was to exploit the benefits of additive manufacturing for the production of an osteoconductive nanocomposite for the potential use in bone tissue applications. This was achieved by adapting a previously developed method that was used to deposit multi-walled carbon nanotubes (MWCNT) onto PA12 particles by Bai et al. [1]. The advantages of using this coating method include its relative simplicity and the ability to produce large quantities of powder over a relatively short period. Furthermore, this method was shown to leave nanoparticles exposed on the surface of the final part without the need for post-processing, which may be highly advantageous for guiding cell-material interaction. The overall aim was to produce a nanocomposite which was suitable as a bone substitute material and served to further expand the current range of materials available for laser sintering, specifically for biomedical applications, and provide further insight into the effects that nanocoated powders can have on the laser sintering process.